Subsecond reorganization of the actin network in cell motility and chemotaxis - Diez, Stefan (National Academy of Sciences, 2005)
Actin networks are continuously reorganized in cells that rapidly change their shape. Applying total internal reflection fluorescence microscopy at acquisition rates of 10–20 Hz, we measured an average growth rate of 3 μm·sec(–1) for filamentous actin structures throughout the entire substrate-attached cortex of Dictyostelium cells. New filaments often proceed along preexisting ones, resulting in bundle formation concurrent with filament growth. In cells that orientate in a gradient of chemoattractant, prominent assemblies of actin enriched in the Arp2/3 complex are inserted into the network, primarily at the base of filopods that point into the direction of the gradient. We propose that high turnover rates of actin filaments confer the plasticity to the cell cortex that is required for rapid accommodation to external stimuli.